Review of techniques for monitoring patient vital signs used by intensive care nurses - part two - Grzegorz Ulenberg; Agata Ulenberg; Łukasz Czapiewski; Marzena Humańska; Wojciech Kaczmarek (Kazimierz Wielki University, 2018)
The work consists of three parts, which discusses such matters relating to the functioning of the cardiovascular, respiratory and central nervous system. A nurse is a person who is directly involved in the conduct, measures and draws attention to possible complications, since it is she is the person who spends the most time at the bedside. Development of medical science involves the construction of specialized medical equipment ever more perfect, more expensive, more complicated to build and operate, requiring more and more qualifications treatment team.